Growth and survival rate of abalone (haliotis squamata) On different stocking density - Atika '; Rusliadi '; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Information about stocking densities that are ideal for the cultivation for abalone isstill very limited. This aim of the study is to determine the stocking density both in themaintenance of abalone. The benefits of this research is to provide information about thestocking density is good for the growth of the abalone and can be reference in the cultivationand further research. This study was conducted over 60 days from February to April 2014,which took place in Mariculture Center in Batam, Riau Islands Province. The method used isan experimental method with a completely randomized design (RAL) with three levels of thetreatment. Treatment 1 (stocking density of 80 animals), treatment 2 (stocking density of 90fish), Treatment 3 (stocking density of 100 fish) . Each treatment had 3 replications.Extensive research treatment of each area ith size of 50 x 35 cm2 in volume. Stocked abaloneseed size from 1.9 to 3 cm and weight from 2.04 to 2.12 g, aged 3-4 months and totaling 810tails. The best results were obtained in treatment 1 with length growth of the average size of2.29 cm to 2.98 cm and the growth of an average weight of 2.07 grams to 3.94 grams.Keywords: Abalone, stocking density, seed, growth